"After all, we are all sick": multi-stakeholder understanding of stigma associated with integrated management of HIV, diabetes and hypertension at selected government clinics in Uganda - Mathias Akugizibwe; Flavia Zalwango; Chaka Moreen Namulundu; Ivan Namakoola; Josephine Birungi; Joseph Okebe; Max Bachmann; Murdoch Jamie; Shabbar Jaffar; Marie Claire Van Hout (BMC, 2023)
Abstract Background Integrated care is increasingly used to manage chronic conditions. In Uganda, the integration of HIV, diabetes and hypertension care has been piloted, to leverage the advantages of well facilitated and established HIV health care provision structures. This qualitative study aimed to explore HIV stigma dynamics whilst investigating multi-stakeholder perceptions and experiences of providing and receiving integrated management of HIV, diabetes and hypertension at selected government clinics in Central Uganda.  Methods We adopted a qualitative-observational design. Participants were purposively selected. In-depth interviews were conducted with patients and with health care providers, clinical researchers, policy makers, and representatives from international nongovernmental organizations (NGOs). Focus group discussions were conducted with community members and leaders. Clinical procedures in the integrated care clinic were observed. Data were managed using Nvivo 12 and analyzed thematically. Results Triangulated findings revealed diverse multi-stakeholder perceptions around HIV related stigma. Integrated care reduced the frequency with which patients with combinations of HIV, diabetes, hypertension visited health facilities, reduced the associated treatment costs, increased interpersonal relationships among patients and healthcare providers, and increased the capacity of health care providers to manage multiple chronic conditions. Integration reduced stigma through creating opportunities for health education, which allayed patient fears and increased their resolve to enroll for and adhere to treatment. Patients also had an opportunity to offer and receive psycho-social support and coupled with the support they received from healthcare worker. This strengthened patient-patient and provider-patient relationships, which are building blocks of service integration and of HIV stigma reduction. Although the model significantly reduced stigma, it did not eradicate service level challenges and societal discrimination among HIV patients. Conclusion The study reveals that, in a low resource setting like Uganda, integration of HIV, diabetes and hypertension care can improve patient experiences of care for multiple chronic conditions, and that integrated clinics may reduce HIV related stigma.